Photomorphogenesis and crop production process of tomato plants depending on daily light integral - D.A. Tovstyko; A.A. Anisimov; I.G. Tarakanov (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2024)
Background. The study of tomato growth and development under light culture conditions is relevant for further technological improvement of crop cultivation on city farms. The use of closed intensive cultivation systems allows to control both the crop quality and yields. The purpose of the research was to analyze tomato physiological reactions and crop production process under different light conditions. Materials and methods. The determinant early-maturing tomato variety was grown in peat vegetative pots. In experiments, the effect of optical radiation on plants with various combinations of photoperiod and illumination intensity was studied. The daily light integral (DLI) at the installations was 9.5 and 19 mol/m2·day. Results.The DLI increase (light treatment12/440) stimulated biomass accumulation and acceleration of plant development. The light patterns of 18h-146 μkmol/ m2·s and 12h-440μmol/ m2·s contributed to earlier transition to generative development of plants. Comparing the effect of the same DLI (9.5 mol/m2·day) on plants morphogenesis it was noticed that tomatoes were more sensitive to light intensity changes that to the photoperiod. The patterns 18/146 and 12/440 may be prominent according to productivity indicators, high pigments content in green biomass and biochemical substances in fruits. Conclusions.The irradiation modes with DLI of 9.5 (light treatments12/220, 18/146) and 19 (light treatment12/440) mol/m2·day have similar effect on plant development. The best adaptation of the determinant tomato to irradiation conditions and the most efficient use of light energy were observed in 12-hour modes in comparison to other patterns.